Why Do People (Not) Engage in Social Distancing? Proximate and Ultimate Analyses of Norm-Following During the COVID-19 Pandemic - Norton, James O.; Evans, Kortnee C.; Semchenko, Ayten Yesim; Al-Shawaf, Laith; Lewis, David M. G. (Frontiers in Psychology, 2021)
COVID-19 has had a profound negative effect on many aspects of human life. While pharmacological solutions are being developed and implemented, the onus of mitigating the impact of the virus falls, in part, on individual citizens and their adherence to public health guidelines. However, promoting adherence to these guidelines has proven challenging. There is a pressing need to understand the factors that influence people’s adherence to these guidelines in order to improve public compliance. To this end, the current study investigated whether people’s perceptions of others’ adherence predict their own adherence. We also investigated whether any influence of perceived social norms was mediated by perceptions of the moral wrongness of non-adherence, anticipated shame for non-adherence, or perceptions of disease severity. One hundred fifty-two Australians participated in our study between June 6, 2020 and August 21, 2020. Findings from this preliminary investigation suggest that (1) people match their behavior to perceived social norms, and (2) this is driven, at least in part, by people using others’ behavior as a cue to the severity of disease threat. Such findings provide insight into the proximate and ultimate bases of norm-following behavior, and shed preliminary light on public health-related behavior in the context of a pandemic. Although further research is needed, the results of this study – which suggest that people use others’ behavior as a cue to how serious the pandemic is and as a guide for their own behavior – could have important implications for public health organizations, social movements, and political leaders and the role they play in the fight against epidemics and pandemics.